Obesity, dietary interventions and microbiome alterations in the development and progression of prostate cancer - Trecarten, Shaun; Liss, Michael A.; Hamilton-Reeves, Jill; DiGiovanni, John (Frontiers in Immunology, 2025)
Purpose of reviewThe role of the microbiome in prostate cancer is an emerging subject of research interest. Certain lifestyle factors, such as obesity and diet, can also impact the microbiome, which has been implicated in many diseases, such as heart disease and diabetes. However, this link has yet to be explored in detail in the context of prostate cancer. The purpose of this review is to explore the cross-talk between obesity, dietary interventions, and microbiome alterations in the development and progression of prostate cancer.Recent findingsMany possible mechanisms exist linking obesity and dietary interventions to microbiome alterations and prostate cancer. The gut microbiome produces metabolites that could play a role in prostate cancer oncogenesis, including short-chain fatty acids, cholesterol derivatives, and folic acid. The microbiome also plays a pivotal role in the prostate tumor microenvironment (TME), contributing to inflammation, local tissue hypoxia, and epithelial-mesenchymal transition. A bidirectional relationship exists between obesity and the microbiome, and certain diets can enact changes to the microbiome, its associated metabolites, and prostate cancer outcomes.SummaryCross-talk exists between obesity, dietary interventions, and the role of the microbiome in the development and progression of prostate cancer. To further our understanding, future human studies in prostate cancer should investigate microbiome changes and incorporate an assessment of microbiome-derived metabolites and cellular/immune changes in the TME.